A comprehensive review of the architecture morphology of the avian kidney : Review - Al-Agele, Ramzi Abdulghafoor Abood (Diyala Journal for Veterinary Sciences, 2024)
A thorough understanding of the architectural morphology of the renal structure is necessary to gain insights into the renal structure. During kidney development in avian embryos, the pronephros, mesonephros, and metanephros arise in succession, as in mammals and reptiles. The mesonephros function for fish and amphibians, whereas the metanephros function for reptiles, birds, and mammals. Birds have elongated, irregularly shaped kidneys that are bigger than the kidneys in mammals and reptiles. Cranial, middle, and caudal kidney lobes make up each kidney, which are blood vessels that cause these divisions. The avian kidney has a dual vascular supply. The renal arteries provide the afferent arterioles of all glomeruli. In reptilian-type nephrons, the veinous supply terminates in the peritubular capillaries. In mammalian-type nephrons, it terminates at least in the proximal tubules. Birds possess renal portals, which are analogous to those seen in reptiles, amphibians, and fish. These portals facilitate renal portal circulation, wherein the renal portal veins transport blood to the kidney tubules, similar to arteries. Bird kidneys have cortical and medullary lobules. Each kidney lobule has a massive cortex and a cone-shaped medullary tract. The base of the medullary cone forms a single collecting duct where lobule nephrons discharge into surrounding collecting ducts. There is no clear line separating the cortical and medullary parts of the lobules. The cortex has Henle loopless reptilian nephrons and Henle loop-containing mammalian nephrons. Birds have pairs of ureters that are symmetrical, and about 17 principal branches vary in length, and subsidiary branches lead to compact cone-shaped collecting tubule tufts. The study attempts to provide any definitive structural correlations that can be determined for the entire group of birds.